Types of fluid-related features controlled by sedimentary cycles and fault network in deepwater Nigeria. (January 2018) - Marsset, T.; Ruffine, L.; Gay, A.; Ker, S.; Cauquil, E.
Abstract: The seismic characteristics of focused fluid-related features such as pockmarks and carbonate build-ups on the Nigerian continental slope have been investigated using complementary seismic data sets (reprocessed 3D exploration data and 2D Very High Resolution hull-mounted and near-bottom seismic data) coupled with the results of previous studies (sedimentological, geotechnical and geochemical analyses). The results show different types of fluid-related features within the hemipelagic phase of long duration (∼1 Myr) Turbidite/Hemipelagic cycles. They are the product of the disturbance of the hosting sediments following two main distinct processes: (1) no or low sediment deposition caused by fluid escape associated with seafloor settlement (benthic fauna, carbonate precipitation, gas hydrate formation) and (2) post-depositional erosion, caused either by fluid release (dewatering from underlying features such as channels and upward migration from a deep source) or by collapse (destabilisation of gas hydrates). The temporal evolution reveals a decrease in fluid flow during the hemipelagic deposition as witnessed by the decrease in methanogenic activity and by gas hydrate destabilisation. The spatial distribution of fluid-related features seems to be controlled by the type of fault (small fault or structural lineament). Highlights: Pockmarks classification was defined using seismic datasets at various scales. Use of geophysical signature of both fluid flow trails and hosting sediments. Depositional or erosional sedimentary disturbances lead to pockmarks formation. Implication of fluid flow and gas-hydrate dynamics on the sedimentary morphology. Control of faults and sedimentary cycles on spatio-temporal evolution.